Development of Problem-Based Learning-Based E-Modules Using Adobe Flash Professional CS6 - Auliani Arafah; Moralita Chatri; Abdul Razak; Violita Violita (Postgraduate, University of Mataram, 2023)
Based on data analysis from observations and interviews with science teachers at SMPN 22 Padang, it can be seen that the student learning process is still passive, and students' interest and motivation in learning are still lacking. Textbooks are the main teaching materials used by both teachers and students. These problems make it difficult for teachers to carry out the learning process, causing students to have difficulty understanding the learning material. This study aims to produce an e-module based on problem-based learning using Adobe Flash Professional CS6 which is valid, practical, and effective for class VIII SMP students. This type of research is design and development research that uses the Plomp development model. The research data were obtained from validity, practicality, and effectiveness tests. Based on the results of the study, showed that the e-module based on problem-based learning had a validity value of 84.24% with very valid criteria based on the validator's assessment. The results of the practicality assessment by the teacher are 90.68% and the results of the practicality assessment by the students are 87.72% with very practical criteria. Problem-based learning-based e-modules that have been developed have effectiveness with very effective categories in terms of competency assessment in the cognitive domain, affective domain, psychomotor domain, and student learning activities